2011
DOI: 10.1159/000332762
|View full text |Cite
|
Sign up to set email alerts
|

Projected Prevalence of Inadequate Nutrient Intakes in Europe

Abstract: Background: The purpose of this study was to analyze the prevalence of nutrient intake inadequacy in Europe, applying the Nordic Nutritional Recommendations in the context of the EURRECA Network of Excellence. Methods: Nutrient data was obtained from the European Nutrition and Health Report II. Those nutritional surveys using a validated food frequency questionnaire or diet history and a food diary/ register with at least 7 days of registers or with an adjustment for intraindividual variability were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
134
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(161 citation statements)
references
References 75 publications
16
134
3
3
Order By: Relevance
“…Among such deficiencies, an inadequate supply of selenium (Se), micronutrient essential for humans and animals, has been associated to a multitude of health disorders, including oxidative stress-related conditions, reduced fertility and immune function, cardiomyopathy, and an increased risk of cancers (Reid et al, 2008;Zeng & Combs, 2008;Rayman, 2012). This deficiency is supported by the studies carried out in Europe by Roman-Viñas et al (2011), which showed inadequate intake of Se in more than 20% of the population. In this context, the Se intake should be highly increased to reach the recommended values.…”
Section: Introductionmentioning
confidence: 99%
“…Among such deficiencies, an inadequate supply of selenium (Se), micronutrient essential for humans and animals, has been associated to a multitude of health disorders, including oxidative stress-related conditions, reduced fertility and immune function, cardiomyopathy, and an increased risk of cancers (Reid et al, 2008;Zeng & Combs, 2008;Rayman, 2012). This deficiency is supported by the studies carried out in Europe by Roman-Viñas et al (2011), which showed inadequate intake of Se in more than 20% of the population. In this context, the Se intake should be highly increased to reach the recommended values.…”
Section: Introductionmentioning
confidence: 99%
“…Ca, vitamins C and D, folic acid, selenium and iodine present the most inadequate intakes, though there no data was available from our region (40). Two years later, another micronutrient mapping in Europe presented a low risk of inadequate intake in all age groups and genders (41).…”
Section: Discussionmentioning
confidence: 76%
“…Roman-Viñas et al [40] conclude that several micronutrients, iodine included, showed a high prevalence of inadequate intakes (above 20%) in Europe. This overwhelming evidence makes prevention of iodine deficiency a high global priority to foster children's development [10].…”
Section: Discussionmentioning
confidence: 99%